1997
DOI: 10.1097/00003072-199708000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Orbital Cavernous Hemangioma With Tc-99m RBC SPECT

Abstract: The authors report two cases of orbital cavernous hemangioma diagnosed by Tc-99m RBC SPECT. Tc-99m RBC SPECT showed a typical scintigraphic pattern commonly seen in hepatic hemangioma in which there is intense focally increased uptake on delayed SPECT images. Tc-99m RBC SPECT in orbital cavernous hemangioma may be as useful a diagnostic modality as in hepatic hemangioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Tc red blood cells is commonly used in the evaluation of hepatic hemangiomas and may also be used in the noninvasive evaluation of extrahepatic vascular lesions such as vascular tumors of the orbit, [13][14][15][16][17][18] as well as in gastrointestinal bleeding imaging, cardiacgated blood pool studies, and radionuclide venograms.…”
Section: Scintigraphy With 99mmentioning
confidence: 99%
See 1 more Smart Citation
“…Tc red blood cells is commonly used in the evaluation of hepatic hemangiomas and may also be used in the noninvasive evaluation of extrahepatic vascular lesions such as vascular tumors of the orbit, [13][14][15][16][17][18] as well as in gastrointestinal bleeding imaging, cardiacgated blood pool studies, and radionuclide venograms.…”
Section: Scintigraphy With 99mmentioning
confidence: 99%
“…This assertion is borne out by several studies reported in the literature. [13][14][15][16][17] Moreover, we may assert that patients with an AI greater than 5.0 are almost certainly affected by cavernous hemangioma. Patients with an AI between 5.0 and 2.0 are likely to be affected by a vascular tumor (hemangiopericytoma, lymphangioma, or cavernous hemangioma).…”
Section: Scintigraphy With 99mmentioning
confidence: 99%
“…[ 99m Tc] is broadly available but the image quality and quantitative accuracy of Single‐photon emission computed tomography (SPECT) are poorer than those of PET imaging. Autologous [ 99m Tc]‐labeled erythrocytes have been used to characterize liver hemangiomas or for the differential diagnosis of orbital cavernous hemangiomas . Additionally, this methodology has been used to identify hemangiomatous lesions in other localizations such as vertebra , spleen and cavernous sinus .…”
Section: Introductionmentioning
confidence: 99%
“…From then onwards, over the past 16 years, we have used Tc-99m RBC scintigraphy routinely to confirm the diagnosis of orbital cavernous hemangioma whenever it was suspected on CT scan. Following our initial work, 3 cases of orbital cavernous hemangioma which were diagnosed by nuclear medicine techniques using red blood cells were recently published (6,7 ).…”
Section: Introductionmentioning
confidence: 99%